2021
DOI: 10.3390/ncrna7020036
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-Coding RNA (lncRNA) Roles in Cell Biology, Neurodevelopment and Neurological Disorders

Abstract: Development is a complex process regulated both by genetic and epigenetic and environmental clues. Recently, long non-coding RNAs (lncRNAs) have emerged as key regulators of gene expression in several tissues including the brain. Altered expression of lncRNAs has been linked to several neurodegenerative, neurodevelopmental and mental disorders. The identification and characterization of lncRNAs that are deregulated or mutated in neurodevelopmental and mental health diseases are fundamental to understanding the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 207 publications
(343 reference statements)
0
41
0
Order By: Relevance
“…Although there is currently less evidence than for miRNAs, altered brain expression of the RNA polymerase III-dependent ncRNA (i.e., NDM29, of the β-site amyloid precursor protein cleaving enzyme-1-antisense lncRNA (i.e., BACE1-AS), and of the intronic ncRNA (i.e., S1A) is known to be correlated to Aβ formation [ 287 , 288 , 289 ]. Moreover, increased cerebral tissue transcription of two lncRNAs, linc00507 and 17A, has been implicated in tau phosphorylation and GABA B alternative splicing, respectively [ 290 , 291 , 292 ]. Concerning possible circulating biomarkers, Feng et al report evidence for significant plasma lncRNA BACE1 upregulation in 88 AD patients when compared to 72 controls [ 257 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although there is currently less evidence than for miRNAs, altered brain expression of the RNA polymerase III-dependent ncRNA (i.e., NDM29, of the β-site amyloid precursor protein cleaving enzyme-1-antisense lncRNA (i.e., BACE1-AS), and of the intronic ncRNA (i.e., S1A) is known to be correlated to Aβ formation [ 287 , 288 , 289 ]. Moreover, increased cerebral tissue transcription of two lncRNAs, linc00507 and 17A, has been implicated in tau phosphorylation and GABA B alternative splicing, respectively [ 290 , 291 , 292 ]. Concerning possible circulating biomarkers, Feng et al report evidence for significant plasma lncRNA BACE1 upregulation in 88 AD patients when compared to 72 controls [ 257 ].…”
Section: Resultsmentioning
confidence: 99%
“…As PTCHD1-AS does not encode for a protein, its contribution to the etiology of ASD and ID is unclear. Emerging evidence suggests that lncRNAs govern the expression of coding genes by altering chromatin status, influencing the initiation of transcription, as well as by affecting mRNA stability post-transcriptionally [ 47 ]. To investigate this, Ross et al employed RNA fractionation and qRT-PCR to conclude that PTCHD1-AS was almost entirely localized to the nucleus, where it was also found to primarily associate with chromatin.…”
Section: Expression Profiling Of Ptchd1 and ...mentioning
confidence: 99%
“…In recent years, studies have shown that long non-coding RNA (lncRNA) plays critical roles in breast cancer progression [ 3 , 4 ], which greatly supplements the gene regulation in this disease. LncRNAs execute their functions via various of paths such as transcription regulation, competitive endogenous RNA regulation and N6-Methyladenosine (m6A) modification [ 5 ]. In this study, the m6A regulation on lncRNA will be demonstrated.…”
Section: Introductionmentioning
confidence: 99%